Lifetime Prediction of Power IGBT Module - WANG Yan-gang; Chamund Dinesh; LI Shi-ping; Jones Steve; DOU Ze-chun; XIN Lan-yuan; LIU Guo-you (机车电传动)
The Weibull methodology for power cycling test data and some reported typical lifetime models were firstly discussed. Then, lifetime prediction procedures were presented including the conversion of mission profile to temperature profile, the temperature cycles counting by Rainflow algorithm, and lifetime calculating based on the fatigue linear accumulation damage theory and lifetime models. Lastly, as an example, power cycling lifetime of 3 300 V/1 200 A IGBT modules manufactured by Zhuzhou CSR Times Electric Co., Ltd., subjected to the application of HXD1C locomotive was predicted.